Aerosolized Vasodilators for the Treatment of Pulmonary Hypertension in Cardiac Surgical Patients: A Systematic Review and Meta-analysis. (August 2017) - Elmi-Sarabi, Mahsa; Deschamps, Alain; Delisle, Stéphane; Ased, Hosham; Haddad, François; Lamarche, Yoan; Perrault, Louis P.; Lambert, Jean; Turgeon, Alexis F.; Denault, André Y.
Abstract : BACKGROUND: In cardiac surgery, pulmonary hypertension is an important prognostic factor for which several treatments have been suggested over time. In this systematic review and meta-analysis, we compared the efficacy of inhaled aerosolized vasodilators to intravenously administered agents and to placebo in the treatment of pulmonary hypertension during cardiac surgery. We searched MEDLINE, CENTRAL, EMBASE, Web of Science, and clinicaltrials.gov databases from inception to October 2015. The incidence of mortality was assessed as the primary outcome. Secondary outcomes included length of stay in hospital and in the intensive care unit, and evaluation of the hemodynamic profile. METHODS: Of the 2897 citations identified, 10 studies were included comprising a total of 434 patients. RESULTS: Inhaled aerosolized agents were associated with a significant decrease in pulmonary vascular resistance (−41.36 dyne·s/cm 5, P = .03) and a significant increase in mean arterial pressure (8.24 mm Hg, P = .02) and right ventricular ejection fraction (7.29%, P < .0001) when compared to intravenously administered agents. No significant hemodynamically meaningful differences were observed between inhaled agents and placebo; however, an increase in length of stay in the intensive care unit was shown with the use of inhaled aerosolized agents (0.66 days, P = .01). No other differences were observed for either comparison. CONCLUSIONS: The administration of inhaled aerosolized vasodilators for the treatment of pulmonary hypertension during cardiac surgery is associated with improved right ventricular performance when compared to intravenously administered agents. This review does not support any benefit compared to placebo on major outcomes. Further investigation is warranted in this area of research and should focus on clinically significant outcomes. Abstract : Supplemental Digital Content is available in the text.Published ahead of print June 7, 2017.